2011
DOI: 10.1002/adma.201103620
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing High‐Resolution, Large‐Area Graphene Patterns by Coffee‐Ring Lithography

Abstract: Taking advantage of the "coffee-ring" effect, graphene electrodes with channel lengths as low as 1-2 micrometers are patterned by inkjet printing. Organic thin film transistors and complementary inverters are also fabricated using these graphene electrodes and show excellent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
130
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 35 publications
1
130
0
2
Order By: Relevance
“…Optical fibre Inkjet printing. Inkjet printing is highly promising for the highthroughput deposition of micron-sized patterns by virtue of its speed, low cost, additive and direct writing capability 38 (Fig. 5a-d) without any chemical/physical modification.…”
Section: Production Of Ltmdsmentioning
confidence: 99%
“…Optical fibre Inkjet printing. Inkjet printing is highly promising for the highthroughput deposition of micron-sized patterns by virtue of its speed, low cost, additive and direct writing capability 38 (Fig. 5a-d) without any chemical/physical modification.…”
Section: Production Of Ltmdsmentioning
confidence: 99%
“…6,7 Mineral rings left on washed glassware or sweat stained clothes are convenient examples of physical systems displaying such a behavior. Understanding the formation of the ring-like patterns from a colloidal droplet is important for many applications such as printing, [8][9][10] genotyping, 11 and colloidal self-assembly, 12,13 for which the distribution of the solute during drying process has to be put under control. Recently it was even demonstrated that the pattern formed by drying of biological fluids can be used as a means of disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in direct patterning techniques have been reported for organic materials, functional polymers, and even tissue engineering [16]. range of a few tens of micrometers [17]. This is one trade-off between expensive and complex processes and ease of patterning.…”
Section: Review Of 3d Structuring Technologies At the Micro/nanoscalementioning
confidence: 99%